Alternative External Resource Allocation Method to Information Security in Smart Cities. (26th April 2022) - Li, Jun; Zou, Kai; Xing, Lining
Abstract : There are alternative external resources among smart cities; that is, no matter which cities are invaded illegally, other cities can avoid losses. Keeping this in mind, urban resource allocation is studied. To be specific, the external resource substitution rate model among smart cities is introduced when describing and modeling the problem, and then, the influences of the independent strategy and joint strategy are analyzed. Based on a comparison of the Nash equilibrium solutions for the above two strategies, a cooperative mechanism is proposed to deal with the problem of overallocation of resources in the process of independent strategy. Finally, the conclusions are verified by numerical experiments.